2017
DOI: 10.1007/s40262-017-0593-6
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Mycophenolic Acid: An Update

Abstract: The most recent comprehensive reviews on the population pharmacokinetics of mycophenolic acid (MPA) were published in 2014. Since then, several population pharmacokinetic studies on MPA have been published. The majority of literature is still focused on the kidney transplant population, although studies have also been conducted in liver and lung transplantation, autoimmune diseases, and hematopoietic stem cell transplant. While the majority of the model building is still based on parametric non-linear mixed-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 29 publications
8
35
0
Order By: Relevance
“…The pharmacokinetic (PK) analysis of gastric bypass patients suggested that higher doses of tacrolimus, sirolimus, and mycophenolate mofetil (MMF) were required in order to provide a similar exposure to the healthy, nonbypass control. 15 Clinical visits after bariatric surgery were scheduled at 1 month, then every 3 months. Neither formulation affected the bioavailability of MMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetic (PK) analysis of gastric bypass patients suggested that higher doses of tacrolimus, sirolimus, and mycophenolate mofetil (MMF) were required in order to provide a similar exposure to the healthy, nonbypass control. 15 Clinical visits after bariatric surgery were scheduled at 1 month, then every 3 months. Neither formulation affected the bioavailability of MMF.…”
Section: Introductionmentioning
confidence: 99%
“…MPA-glucuronides (MPAG) bind extensively to albumin and undergo enterohepatic recirculation by means of the transporter, multidrug-resistant protein-2, and is eliminated in the urine. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Although various popPK models have been developed to quantitatively describe the PK characteristics of MPA over the past decades, whether they can be appropriately extrapolated to other centres remains unclear . Assessing the model transferability may also facilitate the identification of potential centre‐based factors influencing model predictability.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that hepatic UGT1A9 shows a high variability (5–15 fold) in mRNA levels, relative protein content, and in vitro activity (Aueviriyavit, Furihata, Morimoto, Kobayashi, & Chiba, ; Court, ; Girard et al, ) which can cause high variability in MPA PK in transplant patients (Bernard & Guillemette, ). Previous studies showed MPA shows high intersubject variability of tMPA of 2–3 orders of magnitude along the whole concentration–time profile (de Winter et al, ; Kiang & Ensom, ) that can be attributed to variability in UGT1A9 activity (Baldelli et al, ). Other studies showed that no single variable (UGT1A9, UGT2B7, or MRP‐2 activity) alone explained the observed high variability in the exposure of the pharmacologically active fMPA in plasma (Frymoyer, Verotta, Jacobson, & Long‐Boyle, ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed MPA shows high intersubject variability of tMPA of 2-3 orders of magnitude along the whole concentrationtime profile (de Winter et al, 2008;Kiang & Ensom, 2018) that can be attributed to variability in UGT1A9 activity (Baldelli et al, 2007).…”
Section: Discussionmentioning
confidence: 97%